"The biggest hire in school history" : considering the factors influencing the hiring of a major college football coach - Hambrick, Marion E. (SAGE Knowledge. Cases., 2014)
The purpose of this case is to illuminate the numerous factors administrators must consider when conducting and completing a coaching search. Specifically, participants are instructed to use Kellison's (2013) ethical decision-making process framework to guide their analysis when deciding on, and eventually hiring, a head coach at an exceedingly visible university and athletic department. A hypothetical situation was created based on actual events that took place during a highly publicized head coach search in a major university football program. In all, participants will be immersed in the process of identifying, interviewing, and ultimately choosing a new head coach for their highest revenue-generating program during the most important time in the history of the university and athletic department.